Effect of screw press extraction process parameters on pistachio oil recovery and quality. - Fantino, V. M. (2020)
Pistachio nuts have high economical and nutritional value, mostly due to their elevated oil content (50%), which is composed mainly of oleic and linoleic fatty acids. Box-Behnken experimental designs were performed to optimize the oil extraction by response surface analysis. The independent variables measured were seed moisture content (SMC), restriction die (RD), screw press speed (PS) and pressing temperature (PT), while the response variables considered were oil recovery (OR), fine solid contents in the oil (FSC), oil remaining in the cake (OC) and parameters related to oil quality (free fatty acid composition (FFAC, mg KOH/g oil), peroxide value (PV, meq O2/kg oil), K232, K270 and pigment contents, mg/kg oil). Given that the chemical quality of pistachio nut oil pressed under different conditions was not affected, the process response was optimized in order to maximize OR under two pressing temperatures. Therefore, at 75 °C, pistachio oil extraction showed a maximum OR (79.61 g/100 g oil) at 8% SMC, 4 mm RD and 20 rpm SP; while, under cold-pressed conditions, the maximum OR (65.97 g/100 g oil) was achieved at 10% SMC, 4mm RD and 20 rpm SP. It is important to highlight that OR values were higher than the results reported previously and the chemical quality parameters from both oils were in the range of Codex standards for virgin (non-refined) oils (FFAC < 0.31 and PV < 0.33).